Iron‐Mediated Oxidative C–H Alkylation of S, S‐Functionalized Internal Olefins via C(sp2)–H/C(sp3)–H Cross‐Coupling. Issue 17 (11th August 2017) - Wang, Quannan; Lou, Jiang; Wu, Ping; Wu, Kaikai; Yu, Zhengkun
Abstract: Mediated by a catalytic amount of FeCl3, the C–H alkylation of S, S ‐functionalized internal olefins, i.e., α‐oxo ketene dithioacetals and their analogues, was efficiently achieved using simple ethers and toluene derivatives as the coupling partners, di‐ tert ‐butyl peroxide (DTBP) as the oxidant, and DABCO⋅6 H2 O as the additive. The alkylthio functionality is essential for the internal olefinic C–H bond to undergo such an alkylation with the O ‐adjacent C(sp 3 )–H bonds of the ethers and the benzylic C–H bonds of the toluene derivatives, respectively. Tetrasubstituted olefins were thus synthesized and further transformed to highly substituted pyrazoles and isoxazoles. The strategy to activate an internal olefinic C–H bond by polarizing its parent olefinic C=C bond with both the dialkylthio group and an electron‐withdrawing functionality was investigated. The mechanistic studies suggest a radical pathway for the C( sp 2 )–H/C( sp 3 )–H cross‐coupling reactions. The present protocol provides a convenient route to tetrasubstituted olefins. Abstract :